2015
DOI: 10.1590/2317-1782/20152014114
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the acquisition of sonorant consonants orthography in Brazilian children from a São Paulo municipality

Abstract: PURPOSE: To describe the spelling performance of children with regard to the record of sonorant consonants in Brazilian Portuguese language, to verify if the errors in their records were influenced by the accent in the word, and to categorize the kinds of errors found. METHODS: For this current survey, 801 text productions were selected as a result of the development of 14 different thematic proposals, prepared by 76 children from the first grade of primary school, in 2001, coming from two schools of a city fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 17 publications
2
9
0
8
Order By: Relevance
“…It was also observed that the phonological errors that alter the phoneme were more frequent than the errors that alter the syllabic structure, followed by the contextual-arbitrary and the phonetically motivated ones. Some studies (3,13,25,26) have analyzed errors in writing. One of them (13) described the orthographic performance of children without complaints of language and/or learning difficulties reported by parents and/or teachers and concluded that among the errors found in writing were phonological substitutions followed by omissions and substitutions orthographic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also observed that the phonological errors that alter the phoneme were more frequent than the errors that alter the syllabic structure, followed by the contextual-arbitrary and the phonetically motivated ones. Some studies (3,13,25,26) have analyzed errors in writing. One of them (13) described the orthographic performance of children without complaints of language and/or learning difficulties reported by parents and/or teachers and concluded that among the errors found in writing were phonological substitutions followed by omissions and substitutions orthographic.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, complexity in acquiring writing is a constant concern among educators and researchers. In this sense, some studies (1,3,7,(11)(12)(13) were performed with the purpose of verifying the orthographic performance in tasks of reading, writing and/or phonological awareness. Others (2,14) investigated the relationship between writing performance and family psychosocial factors, while others (12,14) re-analyzed the types of errors committed by children during the writing acquisition process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many and diverse questions on this initial phase of language learning are: typical orthographic development, phonological conscience, orthographic deviations, how the writing process develops, speech pathology programs effectiveness in the students´ performance, relation between speech and writing; relation between orthography and literacy; authorship question on writing and, yet, criteria used issue to consider as pathological, children´s writing mistakes 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Já a dislexia é decorrente da combinação de fatores genéticos e neurológicos, que causam déficits no processamento da informação. Por conta disso, os escolares com dislexia podem apresentar desorganização no nível fonológico, causando problemas na conversão fonografêmica, o que também causará problemas nas representações, acesso e recuperação da palavra por meio do acesso fonológico da informação lexical, ocasionando problemas na aprendizagem da escrita ortográfica (FRANÇA et al, 2004;VAZ et al, 2015).…”
unclassified